Corrosion science and technology - Talbot, David; Talbot, James (CRC Press, 2018)
"Twenty years after its first publication, Corrosion Science and Technology continues to be a relevant practical guide for students and professionals interested in material science. This Third Edition thoroughly covers the basic principles of corrosion science in the same reader-friendly manner that made the previous edition invaluable, and enlarges the scope of the content with expanded chapters on processes for various metals and new technologies for limiting costs and metal degradation in a variety of commercial enterprises not explored in previous editions. This book also presents expertly developed methods of corrosion testing and prediction."--Provided by publisher